Antimicrobial and antioxidant properties of various Greek garlic genotypes. (15th April 2018) - Petropoulos, Spyridon; Fernandes, Ângela; Barros, Lillian; Ciric, Ana; Sokovic, Marina; Ferreira, Isabel C.F.R.
Highlights: Antimicrobial and antioxidant properties of Greek garlics were evaluated. Significant variation among the studied genotypes was observed. Genotype G5 showed the highest total phenolics content and the lowest EC50 values. Significant activity against Proteus mirabilis and Escherichia coli was recorded. Inhibitory properties against Candida albicans and C. kruzei were detected. Abstract: Recent studies show a significant variation in antioxidant and antimicrobial properties between the various garlic genotypes mostly due to differences in chemical composition and bioactive compounds content. The aim of the present study was to evaluate antioxidant properties and antimicrobial activity of garlics collected from the main cultivation areas of Greece, as well as to correlate this activity with their total phenolics content. Genotype G5 showed the highest total phenolics content, which was significantly correlated with the lowest EC50 values for all the tested antioxidant activity assays. Antimicrobial activity was significant, especially against the bacteria Proteus mirabilis and Antibiotic resistant Escherichia coli . In conclusion, significant variation was observed between the studied garlic genotypes, indicating the importance of both growing conditions and genotype on bioactive properties of dry garlic bulbs. This variation could be further exploited in breeding programs in order to select elite genotypes with increased bioactive properties.